2022
DOI: 10.1002/jctb.7089
|View full text |Cite
|
Sign up to set email alerts
|

Formation of algal flocs from activated sludge in synthetic medium and secondary treated wastewater

Abstract: BACKGROUND Photogranules seem to be an alternative solution for wastewater treatment and biomass harvesting. The aim of our work was to investigate the formation of algal flocs as an efficient method for the treatment of wastewater and separation of algal cells. RESULTS The progressive change of activated sludge to algal flocs was evaluated under static and stirring conditions using a synthetic substrate (modified Blue Green‐11 medium) and the secondary effluent from an activated sludge wastewater treatment pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Nitrogen is often the limiting nutrient in aquatic ecosystems, and its availability can strongly influence microalgae growth rates. In fact, many studies have shown that nitrogen availability can significantly affect the growth, biomass productivity, and biochemical composition of microalgae [1,38]. However, it is important to note that excessive nitrogen concentration can also be harmful to microalgae, as it can lead to overstimulation of growth, an imbalance in the nitrogen-to-phosphorus ratio, and the production of harmful metabolites that can inhibit further growth.…”
Section: Effect Of Zno Nps On Nutrient Uptakementioning
confidence: 99%
“…Nitrogen is often the limiting nutrient in aquatic ecosystems, and its availability can strongly influence microalgae growth rates. In fact, many studies have shown that nitrogen availability can significantly affect the growth, biomass productivity, and biochemical composition of microalgae [1,38]. However, it is important to note that excessive nitrogen concentration can also be harmful to microalgae, as it can lead to overstimulation of growth, an imbalance in the nitrogen-to-phosphorus ratio, and the production of harmful metabolites that can inhibit further growth.…”
Section: Effect Of Zno Nps On Nutrient Uptakementioning
confidence: 99%